Ghintang Ghisi Dance of Bhaktapur: A Cultural Tourism Product - Dulal, Lok Nath (Nepal Journal of Multidisciplinary Research, 2023)
Bhaktapur is a world-renowned cultural tourism destination of Nepal that offers to tourists wonderful experience and encounter with tangible and intangible cultural heritage. Due to the high classes wonderful and alluring heritage every year large numbers of tourists have been paying their visit. From the cultural tourism perspective colorful jatras, heart-breathing music and dances are also recognized as the renowned sources of attraction. Bhaktapur has already established its fame as a destination of cultural capital that annually celebrates different festivals with performing music and dances on the special auspicious occasion. Rest of them, Ghintang Ghisi dance is also a renowned and an indigenous cultural identity and practice as well as an important tourism product of the destination. It is danced with holding sticks on the occasion of the Gaijatra festival in the month of Bhadra. Although this dance is still unexposed and explored as a significant cultural tourism product in the field of academia it is identified as its research gaps. It is needed to conduct research to recognize this dance as a prominent tourism product. Therefore, to address the research problems and gaps this paper has been prepared. It is based on primary and secondary data whereas qualitative approach, descriptive, analytical and exploratory research designs have been applied in this study. The required data and information have been collected during the field conducted in 2019 and 2022 by consulting with two key informants.